MUTUAL ENRICHMENT OF EDUCATION, SCIENCE AND TECHNOLOGY IN POST-WAR UKRAINE THROUGH SELF-ORGANIZED INTEGRATION OF CREATIVE INDIVIDUALS - MYGAL, S.; MYGAL, V.; MYGAL, G. (Art and Design, 2024)
Purpose of the work is to search for new ideas of metamodeling of physical and digital reality and the development of interdisciplinary means that increase creative and innovative potential. Methodology includes methods of interdisciplinary analysis and cognitive metamodeling of physical and digital reality. Results. New paradigms, hybrid universals and universities are proposed, as well as the method of formation of integral thinking. Their complementarity opens up new opportunities to increase the efficiency of visual communications dynamics. The connection of the generalized principle of N. Bohr’s supplement with the tectonic ordering of fractal nature and the complementarity of the principles of bionics, heuristics and cognitive science, which opens fundamentally new opportunities for the use of different approaches in the design and subject environment of human life, has been revealed. The proposed metamodels of creative thinking, covering key types of design – informational, dynamic and visual. New opportunities for the development of the theory and practice of environment design and its subject filling on the basis of hybrid structures and metamodels are substantiated. Scientific novelty. The first developed meta-methodology of integration of creative personalities, which contributes to the development of creative potential, improvement of mental health and functional safety. Practical significance. An innovative methodology for identifying the peculiarities of knowing the harmony of fractal nature and its application in the process of development of meta-thinking as the ability to know, analyze and change your thinking have been developed. The integrative coefficient of cognitive distortions and integrative criteria for assessing the creative potential of the individual are introduced. An innovative methodology for identifying obvious and hidden cognitive distortions with the help of a AI-transformer is proposed. The complementarity of these results is the basis of a new idea of self-organization of creative personalities, which is aimed at integration of education in post-war Ukraine into a single European space of higher education and the multiplication of human and intellectual capital of Ukraine.